The associations of negative and disorganization symptoms with verbal fluency in schizophrenia: the mediation effect of processing speed and cognitive flexibility - Ernest Marek Tyburski; Ewa Zawadzka; Adrianna Bober; Ewa Karabanowicz; Piotr Podwalski; Jerzy Samochowiec; Anna Michalczyk; Leszek Sagan; Ashok Jansari; Shane T. Mueller; Michał Harciarek; Błażej Misiak; et al. (BMC Psychiatry)
Abstract Background Psychopathological symptoms appear important for cognitive functions in schizophrenia. Nevertheless, the factors and their impact on relationships between negative or disorganization symptoms and verbal fluency are still debatable. The preliminary objective of the study was to compare verbal fluency, including clustering and switching as cognitive strategies, executive functions, and processing speed between individuals with schizophrenia (SZ) and healthy controls (HC). The main aim of the study was to investigate mediation models and identify whether relationships between negative and disorganization symptoms and verbal fluency in schizophrenia are mediated by cognitive flexibility and processing speed. Methods Semantic (animal and fruit) and phonemic (letter k and letter f) fluency tasks, the Berg Card Sorting Test (BCST), and the Color Trails Test (CTT) were administered in the SZ group (n = 108) and a matched HC group (n = 108). The Positive and Negative Syndrome Scale (PANSS) was applied to measure psychopathological symptoms in schizophrenia patients. Results SZ produced fewer words, had larger cluster size, and fewer switches in semantic fluency than HC. Moreover, the SZ group had longer completion time in CTT 1 and CTT 2 and higher percent of perseverative and non-perseverative errors in BCST than HC. Three mediation models demonstrated good fit indices, suggesting that processing speed and cognitive flexibility were significant mediators for relationships between: (1) psychopathological symptoms and productivity or semantic clustering in animal fluency; (2) negative symptoms and productivity in semantic or phonemic fluency; and (3) disorganization symptoms and productivity in semantic fluency. Conclusions Individuals with schizophrenia are characterized by a specific performance profile on verbal fluency tasks. They manifest poor productivity and problems using cognitive strategies for semantic fluency. Referring to executive functioning, schizophrenia patients exhibit decreased cognitive flexibility, problem-solving, and formulating concepts, as well as slow processing speed. It was found that processing speed and cognitive flexibility may be understood as the neuropsychological mechanisms modifying the relationships between negative symptoms, disorganization symptoms, and semantic and phonemic fluency. Therefore, these results provide a foundation for including cognitive flexibility and processing speed in cognitive remediation for schizophrenia patients.